The ratio analysis – the instrument for effective management - Książek, Piotr; Włach, Rafał; Rzemek, Cezary; Jaroszyńska, Anna; Pękalski, Tomasz; Zdrojkowski, Jarosław; Zygo, Maciej (Polish Journal of Public Health, 2010)
Managing a company is connected with understanding the structure of a company and its functioning in the economic sphere. Assessing the company’s gains and losses is the basic element serving this purpose. The ratio analysis is an efficient tool for carrying out the analysis of financial statements, which helps to estimate the situation of the company and enables taking strategic company decisions. It is a collection of logically related ratios, the values and interrelations of which are the basis for complex estimation of the company’s performance. Since the ratios applied in this method are commonly used, companies can be easily compared with each other. The ratio analysis makes chronological assessment and comparison of a phenomenon or its chosen aspect possible as well.However, it has to be remembered that the ratio analysis is only one of the estimation components of the company and it may serve as a mere introduction to a further analysis. Treating the obtained data as the ultimate results which determine the financial situation of the company is unjustified; they are sufficient for planning the development of the company, either.In the present work the elements of the ratio analysis are presented and characterized in detail. There have been presented the drawbacks (e.g., danger of misinterpretation of the ratio data and lack of out-of-finance factors) and advantages (e.g., fast, cheap and fairly objective) of the method.